1989
DOI: 10.2466/pr0.1989.64.3.699
|View full text |Cite
|
Sign up to set email alerts
|

Work-Role Salience: Comparison of Students in Career-Directed and General Degree Courses

Abstract: The work-role salience of 96 first-year South African university students enrolled for career-directed and general degrees was investigated. Equal numbers of men and women and Afrikaans- and English-speaking students were included in each group. Students enrolled for career-directed degrees obtained significantly higher scores in all but one of the four comparisons on the 1973 Work-role Salience Scale of Greenhaus. There were no significant differences for sex or language group. The implications of these resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…However, Watson and Allan (1989) found that students enrolled for career-directed degrees were significantly higher in work role salience than those enrolled for general degree courses. Research on high school students has found white female and Afrikaans-speaking students significantly more work role salient than their male and Englishspeaking peers respectively (Watson & Stead, 1990).…”
Section: South African Research Backgroundmentioning
confidence: 81%
“…However, Watson and Allan (1989) found that students enrolled for career-directed degrees were significantly higher in work role salience than those enrolled for general degree courses. Research on high school students has found white female and Afrikaans-speaking students significantly more work role salient than their male and Englishspeaking peers respectively (Watson & Stead, 1990).…”
Section: South African Research Backgroundmentioning
confidence: 81%
“…They hypothesized that women are likely to exhibit greater levels of commitment to work than are men in order to meet the obligations imposed on them by various life roles. The idea that women are attaching increasing importance to the role of work in their lives was echoed by Watson and Allan (1989). and evidence that women in college may perceive significantly greater numbers of bamers to career development than men in college perceive has been provided by Luzzo (in press).…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which an individual is committed to the role of work in her or his life, sometimes referred to as work-role or career salience in the literature (Greenhaus & Simon, 1976, 1977Stumpf & Lockhart, 1987;Taylor & Popma, 1990;Watson & Allan, 1989), is a concept that has only recently caught the attention of career counselors (Nevill & Super, 1988;Watson & Stead, 1990). Theoretically, commitment to work plays an important role in the career development process.…”
mentioning
confidence: 99%
“…Role salience research has been conducted on an international scale, resulting in a fairly diverse range of study participants. In addition to the United States, researchers have conducted studies in locations such as Canada (Yaremko & Lawson, 2007), England (Noor, 2004), Australia (Ravinder, 1987; Rodd, 1994), Portugal (Duarte, 1995; Ferreira-Marques, 1989), China (Aryee, 1999), Japan (Holloway, Suzuki, Yamamoto, & Mindnich, 2006), Zimbabwe (Mpofu, 2003), and South Africa (Watson & Allan, 1989; Watson & Stead, 1990; Watson, Stead, & De Jager, 1995). The worldwide interest in role salience could potentially be a result of the Work Importance Study (WIS), a project that consisted of psychologists-researchers in 14 countries who were interested in studying the importance of work.…”
Section: Existing Role Salience Researchmentioning
confidence: 99%